In vitro cytotoxic and apoptotic activity of the Mauritian marine sponge Neopetrosia exigua - Beesoo, Rima; Bhagooli, Ranjeet; Bahorun, Theeshan; Neergheen, Vidushi S. (South African Journal of Science, 2023)
Marine sponges belonging to the genus Neopetrosia represent a quasi-inexhaustible source of novel cytotoxic compounds. Yet studies delineating their molecular mechanisms of action in cancer cells remain scarce. We investigated the cytotoxic and apoptosis inducing potential of the Mauritian marine sponge Neopetrosia exigua derived crude extract, hexane and ethyl acetate fraction. Their cytotoxic activity was screened against four cancer cell lines and two non-malignant cell lines via the Alamar Blue metabolic assay. The level of intracellular reactive oxygen species (ROS) production, endogenous antioxidant enzyme activity (catalase and superoxide dismutase) and mitochondrial membrane potential were determined. The ability of the active extract to induce apoptosis in cancer cells and modulate the expression levels of apoptotic markers (caspases and polyADP-ribose polymerase (PARP)) was further evaluated via western blot. The ethyl acetate fraction (NEEAF) displayed the highest inhibitory effect with an IC50 of 6.87 μg/mL against the liver hepatocellular carcinoma cell line (HepG2). Mechanistically, NEEAF induced morphological hallmarks characteristic of apoptosis, increased ROS production, decreased catalase and superoxide dismutase activity and mitochondrial membrane depolarisation in a concentration-dependent manner compared to the control (p